Comparative biomechanical characteristics of one-arm hang in climbing for beginners and qualified athletes - Kozin, S.; Safronov, D.; Kozina, Z.; Kniaz, H.; Proskurnia, O.; Prontenko, K.; Lahno, O.; Goncharenko, V.; Kholodniy, A. (Acta of Bioengineering and Biomechanics, 2020)
The aim of the study: to identify the basic kinematic characteristics of the one-arm hang in climbing for beginners and qualified climbers. Material and methods: There were analyzed the technique of the one-arm hang in climbing among 20 leading climbers of the World and Ukraine and 20 beginner male amateur climbers. A qualified athlete participated in the demonstration of various models of the one-arm hang performance. By means of Kinovea software 0.8.15, the kinematic characteristics of two models of the technique were analyzed (model 1 for beginner athletes, model 2 for qualified athletes). Results: The presence of significant differences (p<0.001) between beginners and qualified athletes in the magnitude of the angles between the shoulder and clavicle, between the spine and the vertical axis in the phase of fixation of the one-arm hang is revealed. The dynamics of the angle between the shoulder and clavicle from the moment of capture of the climbing hold to the phase of fixation of the hang is shown. A theoretical justification for the correct climbing technique with the regard to the laws of mechanics and the laws of force interaction in kinematic chain is provided. Conclusions: Beginner athletes carry out the one-arm hang mainly due to the ligamentous apparatus of the joints of the shoulder girdle with minimal inclusion of muscles, which is dangerous by trauma to the ligaments of the shoulder joint. Skilled athletes perform the one-arm hang with trunk and leg muscles included which reduces the strain from the ligamentous apparatus and lowers the possibility of injury to the ligaments of the shoulder joint.